Analisis Peluang Bisnis Pendidikan di Era Digital: Tantangan dan Solusinya - Yanti, Aprida; Cania, Duwi; Novita, Lesti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze business opportunities in education in the digital era, as well as the challenges and solutions that can be applied in educational institutions. The research uses a qualitative literature study approach to explore understanding of business opportunities, challenges, and solutions in the education sector. The data collection stages involve studying scientific articles, research reports, and relevant books published in the last five years. The data is analyzed using content analysis techniques with a qualitative descriptive approach through stages of data reduction, data classification, data presentation, and drawing conclusions. The research results indicate that several educational business opportunities, such as agribusiness ventures, waste banks, teaching factories, school cooperatives, and creative educational businesses in Inclusive Schools, have great potential. However, they face challenges in human resource management, negative stigma, lack of student involvement, as well as budget constraints and limited access to technology. The proposed solutions include the implementation of technological innovations, entrepreneurship education, better resource management, and building collaboration and relationships. This study is limited to the use of literature sources from the last five years, so the review results have not yet covered the entire development of educational businesses more broadly and in depth. Therefore, further research is recommended to use empirical or mixed methods approaches involving field data in order to obtain more comprehensive results regarding the opportunities and challenges of educational businesses in the digital era